Unusual developing sites of dengue vectors and potential epidemiological implications - Hamady, Dieng; Abu Hassan, Ahmad; Rahman, GM Saifur; MR, Che Salmah; Al Thbiani, Aziz; Tomomitsu, Satho; Fumio, Miake; Zairi, Jaal; Sazaly, Abubakar (Elsevier, 2012)
Objective: To identify the unusual breeding sites of two dengue vectors, i.e. Aedes albopictus (Ae. albopictus) and Aedes aegypti (Ae. aegypti). Methods: During the second half of 2010, we performed an occasional survey in rural (Teluk Tempoyak) and urban (Gelugor) areas of Penang Island, Malaysia, to identify cryptic breeding sites. Results: In the rural area, we found heterogeneous immature stages of Ae. albopictus in the water bowl of an encaged bird. We also observed Ae. aegypti eggs deposited in the flush tank of a toilet in the urban area. Conclusions: It can be concluded that both breeding patterns can increase contact with hosts (humans and birds) and presumably population densities of Ae. albopictus and Ae. aegypti, thereby potentially boosting the risks for spread and transmission of arboviral diseases.